1984
DOI: 10.1007/bf00171592
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of 4′-epi-doxorubicin in metastatic colorectal carcinoma

Abstract: Twenty-three patients with metastatic colorectal carcinoma were treated with 4'-epi-doxorubicin (Epirubicin, 4'-epi-DX) 90 mg/m2 i.v. every 4 weeks. Out of 18 patients evaluable for response, 11 were previously untreated. One complete response of 21 + months was observed in a patient with rectosigmoid carcinoma. Furthermore there was one minor response in pretreated rectosigmoid series, and 6 patients had stabilization of disease. Median survival for all patients, including early deaths, was 4 months. For pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Topoisomerase‐2A (Top2A) is the cellular target of anthracyclines and two meta‐analyses recently confirmed that breast cancer patients with increased TOP2A gene copy number had increased benefit from adjuvant anthracycline treatment (Di Leo et al., 2011), (Du et al., 2011). A number of small and non‐randomized clinical studies have suggested a 10–20% objective response rate following anthracycline treatment of mCRC (Michaelson et al., 1982), (Wils, 1984) and we have now initiated a prospective phase II clinical trial in which metastatic CRC patients with TOP2A gene amplification in their cancer cells are offered treatment with the Top2 inhibitor epirubicin (EudraCTno. 2013‐001648‐79).…”
Section: Introductionmentioning
confidence: 99%
“…Topoisomerase‐2A (Top2A) is the cellular target of anthracyclines and two meta‐analyses recently confirmed that breast cancer patients with increased TOP2A gene copy number had increased benefit from adjuvant anthracycline treatment (Di Leo et al., 2011), (Du et al., 2011). A number of small and non‐randomized clinical studies have suggested a 10–20% objective response rate following anthracycline treatment of mCRC (Michaelson et al., 1982), (Wils, 1984) and we have now initiated a prospective phase II clinical trial in which metastatic CRC patients with TOP2A gene amplification in their cancer cells are offered treatment with the Top2 inhibitor epirubicin (EudraCTno. 2013‐001648‐79).…”
Section: Introductionmentioning
confidence: 99%